MFGE8 regulates TGF-β-induced epithelial mesenchymal transition in endometrial epithelial cells in vitro. Issue 3 (September 2016) - Yu, Liang; Hu, Rong; Sullivan, Claretta; Swanson, R James; Oehninger, Sergio; Sun, Ying-Pu; Bocca, Silvina
Abstract : This study investigated the role of milk fat globule-epidermal growth factor-factor 8 (MFGE8) in TGF-β-induced epithelial–mesenchymal transition (EMT) of endometrial epithelial cells. These were in vitro studies using human endometrial epithelial cells and mouse blastocysts. We investigated the ability of TGF-β to induce EMT in endometrial epithelial cells (HEC-1A) by assessment of cytological phenotype (by light and atomic force microscopy), changes in expression of the markers of cell adhesion/differentiation E- and N-cadherin, and of the transcription factor Snail (by immunofluorescence and immunoblotting), and competence to support embryo attachment in a mouse blastocyst outgrowth assay. We also studied the effects of E-cadherin expression in cells transfected by retroviral shRNA vectors specifically silencing MFGE8. Results demonstrated that TGF-β induced EMT as demonstrated by phenotypic cell changes, by a switch of cadherin expression as well as by upregulation of the expression of the mesenchymal markers Snail and Vimentin. Upon MFGE8 knockdown, these processes were interfered with, suggesting that MFGE8 and TGF-β together may participate in regulation of EMT. This study demonstrated for the first time that endometrial MFGE8 modulates TGF-β-induced EMT in human endometrium cells.